Assessment of the influence of healthcare financing strategies on universal health coverage: a case of Garissa County, Kenya - Dahiye, Aden Mohamed; Mbaruk, Suleiman; Nyamai, Joseph Juma (International Journal Of Community Medicine And Public Health, 2024)
Background: Universal health coverage aims to ensure that all people can use the promotive, preventive, and curative health services they need, while also ensuring that the use of these services does not expose the user to financial hardship. This study aimed to assess the influence of healthcare financing strategies on universal health coverage in Garissa County, Kenya. Methods: The research design for this study was an analytical cross-section study. The study used a mixed research methodology approach where both qualitative and quantitative data were obtained for triangulation purposes. Purposive, systematic, and simple random sampling techniques were employed to recruit study participants in this study. Results: The findings indicated that UHC coverage in Garissa County had been achieved only to a moderate extent. The results indicated that public healthcare financing had a positive and significant influence on UHC coverage in Garissa County (β=0.459; p<0.05). The results indicated that healthcare financing through aid had a positive and significant influence on UHC coverage in Garissa County (β=0.249; p<0.05). The results indicated that private healthcare financing had a negative and not significant influence on UHC coverage in Garissa County (β=-0.092; p>0.05). Conclusions: The results led to the conclusion that public and healthcare aid financing were the most appropriate financing approaches to achieve a notable improvement in UHC coverage in the county. The study also concluded that private health financing had a negative impact on the attainment of UHC.